Nuclear Deterrence and A Prospective Assessment of the Russian-Ukrainian War - Ercan, Ali; Gülboy, Burak Samih (Journal of Applied And Theoretical Social Sciences, 2023)
Nuclear weapons, which people first became acquainted with in history with the attack on Hiroshima and Nagasaki by the United States of America towards the end of the Second World War, have been a deterrent tool, especially with this painful experience in which 220,000 civilians lost their lives, and have been used for this purpose when needed by those countries who possess them. Nuclear deterrence was most intensely used as a deterrent tool, especially during the Cold War and between the two great superpowers of the time, the Soviet Union and the United States. With the developments after Russia intervened in Ukraine in February 2022 and the wide support packages provided by Western countries to Ukraine, the President Vladimir Putin stated that the use of nuclear weapons is now among the options. In this study, firstly, concepts such as nuclear strategy, nuclear weapons, nuclear power, and nuclear deterrence will be discussed in the context of the conceptual framework; by following that, a prospective evaluation of the Russia-Ukraine war will be made in the context of nuclear deterrence.